INTEREST RATE: A KEY VARIABLE IN DEPOSIT MONEY BANKS’ LENDING BEHAVIOUR IN NIGERIA - arikpo, Oka felix; Udoka, Chris O.; Bassey, Ibor I (Archives of Business Research, 2015)
Abstract This study examines the relationship between interest rate and bank loans in Nigeria from the periods 1981 to 2013. The specific objectives were to assess the extent to which monetary policy rate, lending rate, deposit rate and Treasury bill rate relates with the loans and advances granted by banks in Nigeria. To achieve the above objectives, relevant literatures were reviewed. An ex-post facto research design was used for the study. The time series data used were sourced principally from the CBN statistical Bulletin and tabulated using the desk survey. The data were analyzed using the ordinary least square multiple regression statistical technique at 5% level of significance. Result from the analyses reveal that increase in monetary policy rate reduces the capacity of banks to lend; deposit rate and Treasury bill rate have an inverse but significant relationship with bank loans and advances; lending rate had a positive and significant relationship with bank loan and advances in Nigeria. Based on these findings, it is recommended that effort should be made to reduce the lending rate or strengthen the regulatory framework of commercial banks lending rate. Also the spread between lending rate and deposit rates should be narrowed as this will encourage more deposit mobilization and efficient bank intermediation which will enhance bank profitability and economic growth in the long run. Key words: Loans and advances, Lending rate, Deposit rate, monetary policy rate, treasury bills rate, lending behaviour.